ФИЗИЧЕСКАЯ АКТИВНОСТЬ КАК ОДИН ИЗ ФАКТОРОВ ЗДОРОВОГО ОБРАЗА ЖИЗНИ И ВОСПИТАНИЯ МОЛОДЁЖИ - Амонтурдиев, Б.К. (SCIENCE and SOCIETY, 2019)
The active involvement of all layers of the population in physical education and sports, the promotion of the importance of physical education and mass sports in human and family life in all regions of the country is one of the basic conditions for physical and spiritual health and maturity. Creating the necessary conditions for the realization of their abilities and talents, including in the field of sports such systemic solutions, as creating conditions, recruiting individual talents in sports and improving the target training system, as well as focusing on improving the education system and upbringing of the young generation will ensure the prosperity of the Motherland.
Keywords: education; development; sport; activity; physical culture